Educational Digitization and Mobile Learning: Trends in The Political Narratives of International Organizations (Foro de Educacion, 2023)
This paper aims to address a line of reflection framed in the theoretical discourse of the field of international politics, focused on analyzing the role played by International Organizations (UNESCO, European Commission and OECD) in digital education and mobile learning. Methodologically, the content of the published reports on digital education of the three aforementioned organizations has been codified taking as a starting point some recurrent elements; the pedagogical interest (pedagogical dimension) the social capital (learning contexts) and the economic value (actors). The results show that educational digitization is transcending the elements of pedagogical interest related to school innovation plans to be enshrined as a political instrument in the conceptualization of divergent lines and frameworks of digital action. The discussion proposes a line of research around educational digitization as a legitimizing element of the new deglobalizing theses.